Isomeric methoxy analogs of nimesulide for development of brain cyclooxygense-2 (COX-2)-targeted imaging agents: Synthesis, in vitro COX-2-inhibitory potency, and cellular transport properties. Issue 21 (1st November 2015) - Yamamoto, Yumi; Hisa, Takuya; Arai, Jun; Saito, Yohei; Yamamoto, Fumihiko; Mukai, Takahiro; Ohshima, Takashi; Maeda, Minoru; Ohkubo, Yasuhito
Graphical abstract: Abstract: Nimesulide analogs bearing a methoxy substituent either at the ortho -, meta - or para -position on the phenyl ring, were designed, synthesized, and evaluated for potential as radioligands for brain cyclooxygenase-2 (COX-2) imaging. The synthesis of nimesulide and regioisomeric methoxy analogs was based on the copper-mediated arylation of phenolic derivatives for the construction of diaryl ethers. These isomeric methoxy analogs displayed lipophilicity similar to that of nimesulide itself, as evidenced by their HPLC log P 7.4 values. In vitro inhibition studies using a colorimetric COX (ovine) inhibitor-screening assay demonstrated that the para -methoxy substituted analog retains the inhibition ability and selectivity observed for parent nimesulide toward COX-2 enzyme, whereas the meta - and ortho -methoxy substituents detrimentally affected COX-2-inhibition activity, which was further supported by molecular docking studies. Bidirectional transport cellular studies using Caco-2 cell culture model in the presence of the P-glycoprotein (P-gp) inhibitor, verapamil, showed that P-gp did not have a significant effect on the efflux of the para -methoxy substituted analog. Further investigations using the radiolabeled form of the para -methoxy substituted analog is warranted for in vivo characterization.